2020
DOI: 10.1097/ico.0000000000002440
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Visualization of Descemet Membrane Endothelial Keratoplasty Tissue: Assessing the Impact of Trypan Blue Exposure on Stain Duration and Corneal Endothelial Cell Function

Abstract: Purpose: To assess how trypan blue staining affects Descemet membrane endothelial keratoplasty (DMEK) graft visibility and corneal endothelial cell (CEC) mitochondrial respiration. Methods: DMEK grafts (n = 20) were stained with trypan blue 0.06% for 1, 3, 5, or 10 minutes. Each graft was injected into an artificial anterior chamber. Surgery was simulated with tapping and sweeping motions on the corneal surface and injections of balanced salt solution (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Trypan blue is safe and widely used at eye banks during DMEK preparation. 10,11 We previously reported that trypan blue can become toxic to the corneal endothelium when applied for long durations especially at higher concentrations. 10,11 However, a standardized additional 30 seconds of application can likely be applied to most DMEK protocols without approaching the established limits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trypan blue is safe and widely used at eye banks during DMEK preparation. 10,11 We previously reported that trypan blue can become toxic to the corneal endothelium when applied for long durations especially at higher concentrations. 10,11 However, a standardized additional 30 seconds of application can likely be applied to most DMEK protocols without approaching the established limits.…”
Section: Discussionmentioning
confidence: 99%
“…Trypan blue dye at the concentration of 0.06% is safe for use on corneal endothelium and does not compromise corneal endothelial cell mitochondrial functioning. 10,11 Trypan blue staining pattern can provide a much more comprehensive view of endothelial damage that occurred during DMEK preparation when compared with specular microscopy. The purpose of this research was to validate an alternative method for endothelial assessment after DMEK graft preparation using 0.06% trypan blue dye and visual quantification of ECL by eye bank technicians.…”
mentioning
confidence: 99%
“…The use of prestripped and preloaded tissue grafts from eye banks has reduced operative time and tissue wastage. 14,15 Studies have demonstrated how optimal application of trypan blue dye can improve visibility and help surgeons with graft orientation, 16,17 and graft marking can prevent upside-down implantation and reduce primary graft failure. 18 Despite the rapid increase in DMEK prevalence in the United States, the technological and training requirements for DMEK procedures have led to wide variation in the uptake rate around the world.…”
Section: Discussionmentioning
confidence: 99%
“…Lutein/trypan blue staining persisted even if excited EDM tissues were extensively washed before DMEK grafting. This finding represents a great value as DMEK surgery involves the manipulation of EDM-stained grafts inside the anterior chamber for at least 7 min, the mean time required for the unrolling of the flap and its correct positioning in contact with the recipient’s cornea [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%